Proyecto de Factibilidad para una Empresa Procesadora de Café Kosher. - Riofrío Pacheco, Cristian Rolando (2020)
The objective of this project was to establish the feasibility to expand the offer of a coffee processing company, including within its products Kosher certified coffee. For this purpose, the financial, technical and economic feasibility of the market was analyzed. From which, the target market was established, the unsatisfied demand, the installed capacity, the required processes; as well as the strengths, opportunities, weaknesses and threats in order to establish strategies that contribute to the introduction of the product in the market and achieve competitiveness and sustainability. The investigative approach that was used was qualitative, exploratory, descriptive that was based on the analysis of bibliographic sources of information that allowed us to recognize the reality of the environment in which the company operates. The financial evaluation of the project demonstrated its viability, the Net Present Value reaches USD246,857.09, with an IRR of 123.46% and the investment recovery period is one year, three months and 23 days.